Retinoprotective therapy of glaucoma - A.S. Makarova (РМЖ "Клиническая офтальмология")
A.S. Makarova Krasnov Research Institute of Eye Diseases, Moscow, Russian Federation Background: a fluctuating blood pressure (BP) and particularly an overnight hypotension is the key adverse factor leading to the progression of glaucomatous optic neuropathy. Aim: to study the effectiveness of a neuroprotective drug (a complex of water-soluble polypeptide fractions) in patients with unstable primary open-angle glaucoma and normalized ophthalmotonus by monitoring the morphological and functional parameters of the retina and optic nerve. Patients and Methods: this six-month study included 30 patients (60 eyes) with primary open-angle stage 2 or 3 compensated glaucoma and unstable course. At the first stage of the study, a daily blood pressure monitoring (DBPM) was used for all patients to assess changes in systemic hemodynamics. The patients were split into 2 groups, each group consisting of 15 individuals, who received a different number of intramuscular (IM) injections of a neuroprotective drug, 5.0 mg: 10 injections in group 1 and 20 injections group 2. A comprehensive examination of patients was carried out at the beginning of the follow-up period, and at 3 and 6 months after the completion of the course of treatment with the drug. It included visometry, tonometry, static perimetry and optical coherence tomography of the retina and optic nerve. Results: based on the DBPM, the normal circadian BP pattern was disturbed in 27 (90%) patients. During the entire follow-up period, both groups demonstrated an improvement in visual acuity. The results of static perimetry indicated the stabilization of the glaucoma process in group 1 patients, while in group 2 where the treatment course with the neuroprotective drug lasted twice longer, it was possible to achieve an improvement in photosensitivity of the retina, as proven by the positive trends in MD and PSD indices. The results of the functional studies fully correlated with the morphological findings as demonstrated by a reliable stabilization of the status of the retinal nerve fiber layer and ganglion complex, as well as the volume of the optic nerve head. At the same time, a longer course of therapy with the drug was accompanied not only by a significant increase in the above parameters, but also by a decline in the volume of excavatio n of the optic nerve disc. Conclusions: the use of the neuroprotective drug in patients with the progression of primary open-angle glaucoma co-occurring with the changes in systemic hemodynamics enabled to achieve stabilization and improvement of the visual functions. Keywords: glaucoma, systemic blood pressure, peptide preparation, retinal ganglion cells, neuroprotection, retinoprotection. For citation: Makarova A.S. Retinoprotective therapy of glaucoma. Russian Journal of Clinical Ophthalmology. 2022;22(4):210–215 (in Russ.). DOI: 10.32364/2311-7729-2022-22-4-210-215.